2022
DOI: 10.3758/s13423-022-02166-1
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of learning reveal conscious access to stimulus memorability

Abstract: The data, stimuli, and experimental codes are posted publicly at the Open Science Framework (https://osf.io/qrxs3/).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…Future studies are necessary to elucidate the effect of category granularity on memorability. Of equal importance, researchers have questioned whether and to what extent humans have explicit access to memorability (Isola et al, 2014;Saito et al, 2023). To answer this, Experiments 2A and 2B first showed that both ResMem and humans reliably predicted memorability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future studies are necessary to elucidate the effect of category granularity on memorability. Of equal importance, researchers have questioned whether and to what extent humans have explicit access to memorability (Isola et al, 2014;Saito et al, 2023). To answer this, Experiments 2A and 2B first showed that both ResMem and humans reliably predicted memorability.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments 2A and 2B reanalyzed the data collected in Experiments 1A and 2A of Saito et al (2023), respectively. For each experiment, 120 young residents of the United States and Canada (Experiment 2A: 18–31 years old, M age = 24.19, SD = 3.97, n female = 61; Experiment 2A: 18–30 years old, M age = 22.68, SD = 3.13, n female = 91) were recruited through Prolific and received monetary compensation (7.50 £/hr).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…People have limited insight into which images are "memorable" or "forgettable" (e.g. Bainbridge et al, 2013;Isola et al, 2013;although see Undorf & Bröder, 2021;Saito et al, 2022), and memorability is independent of mere novelty, arousal, or attention (for a review see Bainbridge, 2019;Bainbridge, 2020;Isola et al, 2011). In fact, memorability has been shown to be a stronger determinant of memory than people's attentional states (Wakeland-Hart et al, 2022), and it may reflect how easy it is to process an image (Goetschalckx et al, 2019;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%